The Role of the Fe/Mo Cations Ordering Degree and Oxygen Non‐Stoichiometry on the Formation of the Crystalline and Magnetic Structure of Sr2FeMoO6−δ. Issue 5 (3rd December 2018) - Kalanda, Nikolay; Turchenko, Vitalii; Karpinsky, Dmitry; Demyanov, Sergey; Yarmolich, Marta; Balasoiu, Maria; Lupu, Nicoleta; Tyutyunnikov, Sergey; Sobolev, Nikolai A.
Abstract : Single‐phase Sr2 FeMoO6− δ powders with various oxygen indices ( δ ) and degrees of the superstructural ordering ( P ) of the Fe/Mo cations are obtained from SrFeO2.52 and SrMoO4 reagents via solid‐state synthesis. It has been established by means of the X‐ray and neutron diffraction that, upon reducing the oxygen content and enhancing the superstructural ordering, the lengths of the Fe–O1 and Mo–O2 bonds in the crystal lattice increase, whereas the Fe–O2 and Mo–O1 bond lengths decrease. At the same time, the volume of the unit cell is reduced, which indicates an enhancement of the covalency degree of the bonds and stimulates a redistribution of the electron density, as well as an increase of the concentration of the spin‐down charge carriers located in the conduction band on the Mo( t 2 g )↓ orbitals. This circumstance leads to an increase of the density of states at the Fermi level, accompanied by an amplification of the exchange interaction and elevation of the Curie temperature, which points to the leading role of the spin‐polarized charge carriers at the Fermi level in the exchange interaction. Abstract : In this paper, it is revealed that the Fe/Mo–O1 and Fe/Mo–O2 bond lengths of Sr2 FeMoO6− δ along the (001) and (110) crystallographic planes shorten with increasing oxygen index and the degree of Fe/Mo superstructural ordering. It leads to a decrease in the unit cell volume that indicates an enhancement of the covalency degree of the bonds and stimulates a redistribution of the electron density.